Unmet psycho-social needs, coping strategies and psychological distress among people with cancer: Evidence from Pakistan - Nida Shahid; Tamkeen Ashraf Malik; Akmal Hussain; Shaf Ahmed (Journal of the Pakistan Medical Association, 2021)
Objective: To explore the unmet psychosocial needs, coping styles and psychological distress among people ith cancer in Pakistan. Methods: A cross-sectional correlational study design was used for data collection. The research was conducted in Shifa International Hospital, Islamabad and Hayatabad Medical Complex, Peshawar with a sample of 182 participants diagnosed with cancer. Only those who consented to participate were approached from May to July, 2017. Supportive Care Needs Survey-Short Form 34 (SCNS-SF34), Mini-Mental Adjustment to Cancer Scale (Mini-Macs) and Hospital Anxiety Depression Scale (HADS) were used for data collection. Results: It was found that all psychosocial needs were unmet among all the participants (100%) who were suffering from cancer illness. Among five sub-domains of psychosocial needs, health information needs (35.61%) and psychological needs (30.7%) emerged to be strikingly unmet. Moreover, anxious preoccupation and hopeless/helplessness were highly endorsed maladaptive coping styles. A statistically significant relationship existed among unmet psycho-social needs, maladaptive coping and psychological distress. Conclusion: This Study outcome pointed towards gaps in delivering quality care services in Pakistani healthcare settings, inadequate attention of health professionals and serious psychological health care neglect of patients fighting with life threatening disease. This negligence may jeopardize patient’s overall health, can raise health care costs and consequently can contribute to elevated psychological distress. Hence, there is a dire need for proper psychological interventions for effective and holistic treatment planning which can improve the whole process of illness and recovery. Keywords: Cancer, Psychosocial support system, Continuous...